Racial Capitalism, Refugee Adjudication, and the Performances of Zama Zama - Sean Metzger (Lateral)
This essay investigates the category of the refugee as an instantiation of racial capitalism. To illustrate this conjunction, it first examines international law that defines refugees and, then, looks to specific national jurisprudence that accords different recognition to them. The national contexts discussed are the United States, given that the racial discourse there serves as a ground for the most widely known theorization of racial capitalism via Cedric Robinson’s book Black Marxism: The Making of the Black Radical Tradition, and South Africa, where racial capitalism was first coined. Robinson’s work is briefly elaborated in relation to subsequent scholarship that has engaged and extended the concept of racial capitalism, in relation to the particularities of South Africa racialization, and in relation to zama zamas (unregulated miners, often perceived as foreigners who threaten the Rainbow Nation’s stability in various ways). Given limitations of space, the essay uses the overview of juridical regimes and the excursus on Robinson to rethink the category of refugee. Zama zamas and the history of the South African mining sector as it informs understandings of race are posited as a fruitful direction for further research because these phenomena help to extend the entwinement of race and refugee and the implications of Robinson’s text for understanding refugees anew.